Leaf Physiological Responses of Three Psammophytes to Combined Effects of Warming and Precipitation Reduction in Horqin Sandy Land, Northeast China - Huang, Wen-Da; He, Yuan-Zheng; Wang, Huai-Hai; Zhu, Yuan-Zhong (Frontiers in Plant Science, 2022)
ABSTRACT The decreasing precipitation with global climate warming is main climate conditions in some sandy grassland ecosystem. The understanding of physiological responses of psammophytes in relation to warming and precipitation is a possible way to estimate the response of plant community stability to climate change. We selected Lespedeza davurica, Artemisia scoparia and Cleistogenes squarrosa in sandy grassland to examine the effect of combination of climate warming and decreasing precipitation on RWC, chlorophyll, proline and antioxidant enzymes activities. We found that all experimental treatments have influenced on relative water content (RWC), chlorophyll, proline and antioxidant enzymes activities of three psammophytes. L. davurica has the highest leaf RWC among the three psammophytes. With the intensification of precipitation reduction, the decreasing amplitude of chlorophyll from three psammophytes was L. davurica ＞ C. squarrosa ＞ A. scoparia. At the natural temperature, the malondialdehyde (MDA) content of the three psammophytes under severe drought treatment was much higher than other treatments, and their increasing degree was as follows: A. scoparia ＞ C. squarrosa ＞ L. davurica. At the same precipitation gradient, proline of three psammophytes under warming was higher than natural temperature. The differences of superoxide dismutase (SOD) among the three psamophytes were A. scoparia ＞ L. davurica ＞ C. squarrosa. Moreover, at natural temperature, more than 40% precipitation reduction was most significant. Regardless of warming or not, catalase (CAT) activity of A. scoparia under reduced precipitation treatments was higher than natural, while the response of L. davurica was opposite. Correlation analyses evidenced that T was significant in L. davurica, W was significant in A. scoparia and C. squarrosa according to the Monte Carlo permutation test (p = 0.002, 0.004, 0.004). The study is important in predicting how local plants will respond to future climate change and assessing the possible effects of climate change on sandy grassland ecosystems.